Solidness investigation of ward thickness on Ferro convection in an anisotropic permeable framework in the presence of flat liquid temperature - J. Azeem, M.; Selvaraj, A. (International Journal of Engineering and Technology, 2026)
The force field dependent viscousness result of ferroconvection in associate aeolotropic disposed porous system has been studied. The layer of fluid is undertaken to be delimited by free partition. The proper manner of constitutional equation is obtained by liner hypothesis theory. The limit worth of the horizontal magnitude relation and vertical temperature changes, aeolotropic particle parameters, magnetic porosity of porous system, increasing issue of magnetic dependent viscousness and therefore the magnetization parameter are studied. This methodology is found to stabilize solely unchanged mode of instability.